Reading habits among children in Niah longhouses in Sarawak - Nangku, Ngendang (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study is a survey that intends to investigate the existing reading habits among children in Niah longhouses in Sarawak. In order to find out the children’s reading frequency, the survey elicited information on the amount of time spent for reading or how frequent do they read. Besides, this study identified the types of reading materials that the students usually read and the reason of choosing the reading materials. On the other hand, the study also discovered the factors that influence the children’s reading habits either the factors encouraging or discouraging their reading habits.Lastly, this study aimed to find if there are any relationships between the children’s reading habits and their achievement in school. The samples for this study were 25 children and their parents/guardians from six selected longhouses in the area. Generally, the children have very positive attitudes towards reading for pleasure. The findings of the study revealed that generally, 84% of the children have spent some amount of time for pleasure reading which is 20 minutes, 30 minutes, 1 hour,2 hours and 3 hours. However, the study indicated that the children still did not have good reading habits even though they have positive attitudes towards reading. On the other hand, schools, family and friends were identified as the sources of the reading materials for the children. The study also revealed the types of reading materials read by the children were divided into two, which were materials for academic reading (i.e. textbook) and materials for non-academic reading (i.e. comic, novel, magazines, storybooks and newspaper). Besides,encouragement given by those around the children, self interest, availability and accessibility of reading materials, and modeling other’s action were identified as the factors encouraging their reading habits. Meanwhile, the study also found out the children’s illiteracy and laziness were the factors that hindered the children from reading. Moreover, there were significant relationships between the children’s reading habits with their achievement in school despite they have admitted it help them in their study.